Effect of dietary intervention on serum lignan levels in pregnant women - a controlled trial - Mäkelä Sari; Smeds Annika I; Saarinen Niina M; Kharazmi Elham; Luoto Riitta; Fallah Mahdi; Raitanen Jani; Hilakivi-Clarke Leena (BMC, 2010)
Abstract Background Mother's diet during pregnancy is important, since plant lignans and their metabolites, converted by the intestinal microflora to enterolignans, are proposed to possess multiple health benefits. Aim of our study was to investigate whether a dietary intervention affects lignan concentrations in the serum of pregnant women. Methods A controlled dietary intervention trial including 105 first-time pregnant women was conducted in three intervention and three control maternity health clinics. The intervention included individual counseling on diet and on physical activity, while the controls received conventional care. Blood samples were collected on gestation weeks 8-9 (baseline) and 36-37 (end of intervention). The serum levels of the plant lignans 7-hydroxymatairesinol, secoisolariciresinol, matairesinol, lariciresinol, cyclolariciresinol, and pinoresinol, and of the enterolignans 7-hydroxyenterolactone, enterodiol, and enterolactone, were measured using a validated method. Results The baseline levels of enterolactone, enterodiol and the sum of lignans were higher in the control group, whereas at the end of the trial their levels were higher in the intervention group. The adjusted mean differences between the baseline and end of the intervention for enterolactone and the total lignan intake were 1.6 ng/ml (p = 0.018, 95% CI 1.1-2.3) and 1.4 ng/mg (p = 0.08, 95% CI 1.0-1.9) higher in the intervention group than in the controls. Further adjustment for dietary components did not change these associations. Conclusion The dietary intervention was successful in increasing the intake of lignan-rich food products, the fiber consumption and consequently the plasma levels of lignans in pregnant women. Trial registration ISRCTN21512277, http://www.isrctn.org